Capturing insects in guava orchard with soil trap (Research, Society and Development, 2020)
The development of equipment for capturing insects, in order to meet the need of technicians and researchers, is of paramount importance to obtain accurate data on the population of insects in a given area. The soil trap is used in order to have a sample of the population size of the macro fauna present in the soil.  The objective of the experiment was to capture insects of different orders with soil traps and to verify the constancy of the orders of insects in the Experimental Area of Guava Orchards of Federal Institute of Education, Science and Technology of Paraiba Campus Sousa, Unit II in São Gonçalo, Paraiba State. For this, six soil traps were installed, arranged in strategic points, with 30 m spacing between them, in a triangle shape. The traps were made of 2-liter plastic bottles (PET) of soft drink, cut in half and 10 cm in diameter and 15 cm high. Inside each bottle 300 mL of water and two tablespoons of neutral detergent were placed to break the surface tension of the water. The main orders of insects were respectively, Hymenoptera with 100% of the total species collected in the soil traps; Neuroptera 66.66%, Orthoptera 33.33% and Diptera with 33.33%. In the experiment, a constant frequency was observed, that is, those present in more than 50% of the collections, in particular the order Hymenoptera, with the red ant species (Formica rufa), followed by lion ant (Myrmeleon brasiliensis).